Penyelesaian Sengketa di Perbankan Syariah - Aprilia Lestari (Universitas Muhammadiyah Enrekang, 2023)
The principles of Islamic banking are part of Islamic teachings related to the economy. One of the principles in Islamic economics is the prohibition of usury in various forms, and using a system, among others, in the form of the principle of profit sharing. Seeing the development of Islamic banks so far, Islamic principles which are the main basis for Islamic banks in carrying out their duties have not been able to be applied and enforced optimally, especially in the event of a dispute between the parties, the Islamic bank and its customers. The author is interested in researching how to enforce the law on sharia banking dispute resolution? This research is a normative juridical law research, which is a study of norms or laws between statutory regulations and other related regulations. The results of the study indicate that efforts to resolve a dispute can be carried out through two channels, namely the judicial route (litigation) and the non-litigation route. In the Islamic tradition, both are also used to resolve a dispute, but a peaceful settlement (shulh) is the best settlement (as-shulhu khair).